Mandibular parameters as a predictor of sex: A digital orthopantomogram study - Ojha, Bidhata; Bajracharya, Dipshikha; Koju, Sushmit; Maharja, Nisha; Saha, Ankit; Baral, Radha (Journal of Kathmandu Medical College, 2021)
Background: The determination of age and sex is required for forensic practice and medicolegal purposes. Because the mandible is typically recovered intact, it plays a crucial role in determining sex. Orthopantomogram X-rays can be used to thoroughly examine the mandible. The availability of a large number of antemortem orthopantomograms could be extremely beneficial in terms of evaluating and developing population-specific sex determination standards. Objectives: To evaluate the usefulness of the mandibular ramus in sex determination by evaluating linear and angular measurements of the mandibular ramus on digital panoramic radiographs. Methods: An analytical cross-sectional study was conducted on 216 digital orthopantomogram from March 2021 to June 2021 in Kantipur Dental College. A convenient sampling technique was used to collect the radiographs. Mandibular parameters were traced using Image J Software, and angular and linear parameters were calculated. Radiographs with high image quality and sharpness of patients with full permanent dentition, no radiographic evidence of trauma were included in the study. Descriptive analysis was done using IBM SPSS Statistics for Windows, version 20 (IBM Corp., Armonk, N.Y., USA). The measures were compared using an Independent t-test, and the results were subjected to discriminant function analysis. Results: The male’s vertical parameters were found to be greater than the female’s. The coronoid height was shown to be the most dimorphic using discriminant analysis. The overall accuracy of the mandibular parameters was 63.4%. Conclusion: Mandible can be used as an adjunct in sex determination.